What Is the Place of Genetics in the Pathogenesis of Pre-Eclampsia? - Broughton Pipkin, F. (Biology of the neonate, 1999)
It is most unlikely that there is a single ‘pre-eclampsia (PE) gene’. We are probably looking for a cluster of polymorphisms which, possibly in conjunction with environmental factors, predispose to the development of the condition. Accurate phenotyping is vital for any genetic studies of PE, and since the disease is only clinically-detectable in the second half of pregnancy, is particularly difficult. It is increasingly likely that there is a fetal genetic contribution which can only be examined after birth. Candidate genes examined on the basis of displayed or hypothetical pathophysiological effects, but for which no evidence of association or linkage has been found have included HLA-DRβ, HLA-G, and tumour necrosis factor alpha (chromosome 6), angiotensin-converting enzyme (chromosome 17) and CuZn superoxide dismutase (chromosome 21). Chromosomal exclusion mapping and a pedigree study suggest a role for genes on chromosomes 1, 3, 4, 9 or 18. Two genes concerned with clotting, those for factor 5 and methylenetetrahydrofolate reductase, lie on chromosome 1. Both have polymorphisms present in significantly higher frequency in women with PE, as well as showing functional abnormality. They probably predispose to the development of the condition, without being necessary for it. The angiotensinogen (Aogen) gene also lies on chromosome 1. The renin-angiotensin system may be activated during the early stages of PE and subsequently suppressed. In some populations, a relatively common polymorphism is present in raised frequency in women with PE, but it is also raised in non-pregnant hypertensive subjects. However, it is in partial linkage disequilibrium with another polymorphism which shows significantly distorted transmission from mother to fetus in PE pregnancies. Furthermore, its expression is significantly raised in the decidual spiral arteries; abnormal placentation is a feature of PE. We have also shown that a relatively common polymorphism in the angiotensin AT1 receptor gene (chromosome 3) is associated with raised density of the receptor. Thus far, studies of candidate genes have been on a small scale and have very much reflected the pathophysiological research interests of the investigators. The multifaceted nature of PE and the difficulties of accurate phenotyping require the accumulation of a large, very carefully phenotyped, database. It is hoped that funding will become available this year in the UK to allow the collection of such a database. The introduction of chip technology should allow genome scanning of the resource.